Characterization of Novel Integrons, In1085 and In1086, and the Surrounding Genes in Plasmids from Enterobacteriaceae, and the Role for attCaadA16 Structural Features during attI1 × attC Integration - Wang, Dongguo; Hou, Wei; Chen, Jiayu; Yang, Linjun; Liu, Zhihui; Yin, Zhe; Feng, Jiao; Zhou, Dongsheng (Frontiers in Microbiology, 2017)
Novel class 1 integrons In1085 and In1086, containing the class D β-lactamase -encoding gene blaOXA, were identified in clinical enterobacterial strains. In this study, we aimed to characterize the genetic contexts of In1085 and In1086, with the goal of identifying putative mechanisms of integron mobilization. Four plasmids, approximately 5.3 kb, 5.3 kb, 5.7 kb, and 6.6 kb, from 71 clinical Enterobacteriaceae strains were found to contain class 1 integrons (In37, In62, In1085, and In1086, respectively). Two of these plasmids, pEco336 and pNsa292, containing In1085 and In1086, respectively, were further characterized by antibiotic susceptibility testing, conjugation experiments, PCR, sequencing, and gene mapping. The OXA-type carbapenemase activities of the parental strains were also assessed. The results revealed that the novel integrons had different genetic environments, and therefore demonstrated diverse biochemical characteristics. Using evolutionary inferences based on the recombination of gene cassettes, we also identified a role for attCaadA16 structural features during attI1 × attC insertion reactions. Our analysis showed that gene cassette insertions in the bottom strand of attCaadA16 in the correct orientation lead to the expression the encoded genes from the Pc promoter. Our study suggests that the genetic features harbored within the integrons are inserted in a discernable pattern, involving the stepwise and parallel evolution of class 1 integron variations under antibiotic selection pressures in a clinical setting.